Application of Merdeka Curriculum in IPAS Learning - Prihantini, Prihantini; Judijanto, Loso; Kadiyo, Kadiyo; Rukmini, Ai; Iqbal, Muhammad; Fauzi, Muhammad Sukron (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to examine the impact of the implementation of the Merdeka Curriculum on student engagement and academic performance in Natural and Social Sciences (IPAS) learning at Wangiwisata Public Elementary School, located in Bandung Regency, West Java, Indonesia. The research adopts a quantitative approach with a pretest-posttest design. Data were obtained through student engagement questionnaires, academic performance tests, and teacher interviews. The population consisted of fourth- and fifth-grade students in elementary schools that had implemented the Merdeka Curriculum for at least one academic year. The sample was selected using purposive sampling, focusing specifically on students and teachers from Wangiwisata Public Elementary School. Data were analyzed using descriptive statistics to measure changes in engagement and academic performance, and Pearson correlation to examine the relationship between these two variables. Thematic analysis was applied to qualitative data from teacher interviews. The results indicate a notable increase in student engagement across cognitive, affective, and behavioral dimensions, with an average increase of over 20%. Academic performance also improved, particularly in critical thinking and problem-solving skills. Teachers reported greater flexibility in designing learning activities, and the active learning approach promoted by the curriculum enabled students to relate learning materials to real-life contexts. These findings suggest that the Merdeka Curriculum has the potential to enhance both student engagement and academic outcomes when implemented effectively, especially in the context of public elementary education in Indonesia.